Comparison of Radio Interferometers with Analog and Digital Extraction of Recorded Signal - N. E. Kol'tso; S. A. Grenkov; L. V. Fedotov (Известия высших учебных заведений России: Радиоэлектроника, 2020)
Introduction. Radio telescopes of Very Long Baseline Interferometry (VLBI) networks usually record several signals with relatively narrow (up to 32 MHz) bands, which are extracted by means of base band converters (BBC) from an analog noise signal of an intermediate frequency (IF) with bands up to 1 GHz. When processing data, frequency band synthesis is used. At new small radio telescopes (for example, RT-13), directly wideband IF signals are digitized. An ability to connect the RT-13 radio telescope to the “Quasar” VLBI complex and to international VLBI networks provides by a digital narrow-band signal extraction module developed in 2019.Aim. Determining the measuring accuracy of an interferometric group delay of a signal by a radio interferometer with a digital narrow-band signal extraction module and comparing the sensitivity of interferometers with analog and digital signal extraction systems.Materials and methods. Sensitivity losses of interferometers with different systems for detecting recorded signals were calculated. The accuracy of a multi-channel interferometer with the synthesis of a frequency band and of an interferometer with recording of digital broadband IF signals without band synthesis was compared. The results were confirmed by VLBI observations in the observatories of the “Quasar” complex.Results. When replacing the analog system of signal extraction with digital system the sensitivity losses of the interferometer were slightly reduced. The measurement accuracy of the interferometric group delay had not changed. Accuracy increased when digitally recording broadband IF signals and when synthesizing a frequency band significantly larger than the IF bandwidth. Conditions and minimum synthesized bands were determined under which the accuracy of the interferometer with the registration of narrowband signals can be higher than the accuracy of the interferometer with the registration of wideband IF signals.Conclusion. The problem of combining RT-13 radio telescopes with VLBI networks with recording of video frequency signals was solved. The efficiency of the installation of digital signal conversion systems at radio telescopes was shown.